Tanggung Jawab Hukum Promotor Konser Korean Pop (K-Pop) atas Kerugian Konsumen akibat Perubahan Sepihak Penyelenggaraan Acara - Rifati Daeli (Jurnal Hukum dan Sosial Politik, 2026)
The rapid growth of Korean Pop (K-Pop) concerts in Indonesia has created increasingly complex legal relationships between concert promoters and consumers through electronic ticket purchase agreements. In practice, promoters frequently include exoneration clauses in ticket sale terms and conditions that permit unilateral changes to concert schedules, venues, seating arrangements, or other essential aspects while limiting their legal liability. Such practices may result in financial and non-financial losses for consumers and raise concerns regarding the effectiveness of consumer protection under Indonesian law. This study aims to analyze the legal protection available to consumers against exoneration clauses and examine the legal liability of K-Pop concert promoters for losses arising from unilateral changes in concert organization. This normative legal research employs statutory, conceptual, and case approaches. The study uses primary, secondary, and tertiary legal materials analyzed through qualitative legal methods. The findings indicate that although exoneration clauses are generally recognized in contractual relationships, their validity is limited by Article 18 of Law Number 8 of 1999 concerning Consumer Protection, as well as the principles of good faith and contractual balance. Unilateral changes that reduce consumers' contractual rights constitute a breach of contract and may impose liability on promoters to compensate consumers under Article 19 of the Consumer Protection Law. Therefore, promoters cannot rely on exoneration clauses to avoid statutory liability for losses caused by unilateral changes. Stronger legal supervision and greater compliance with consumer protection principles are necessary to ensure legal certainty, fairness, and accountability within Indonesia's entertainment industry.